2001
DOI: 10.1161/01.cir.103.23.2828
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Stroke With Gemfibrozil in Men With Coronary Heart Disease and Low HDL Cholesterol

Abstract: In men with coronary heart disease, low HDL cholesterol, and low LDL cholesterol, gemfibrozil reduces stroke incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(101 citation statements)
references
References 39 publications
(26 reference statements)
1
99
0
1
Order By: Relevance
“…It occurs naturally in a trans-or cis-isoform [7][8][9] . Resveratrol has been reported to have several biologic effects such as a potent antioxidative effect via prevention of lipid peroxidation [10,11] , anti-platelet activity [12] , an estrogenic activity [13] , and anti-inflammatory activity attributed to cyclooxgenase inhibition [6,14] . Previously, it was suggested that resveratrol stimulated nitric oxide production in endothelial cells, has a vasodilatory effect on blood vessels [15] , and improves the energy metabolism system after spinal cord trauma [16] .…”
Section: Introductionmentioning
confidence: 99%
“…It occurs naturally in a trans-or cis-isoform [7][8][9] . Resveratrol has been reported to have several biologic effects such as a potent antioxidative effect via prevention of lipid peroxidation [10,11] , anti-platelet activity [12] , an estrogenic activity [13] , and anti-inflammatory activity attributed to cyclooxgenase inhibition [6,14] . Previously, it was suggested that resveratrol stimulated nitric oxide production in endothelial cells, has a vasodilatory effect on blood vessels [15] , and improves the energy metabolism system after spinal cord trauma [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale clinical studies in patients with high triglyceride (TG), low HDL-C and normal LDL-C levels have not shown as much positive evidence as that for LDL-C-lowering therapy [8][9][10][11][12] . However, the subanalysis of the ACCORD Lipid Trial 13) revealed that combination therapy with fibrates and statins is effective in patients with high TG and low HDL-C levels; thus, further investigation is warranted.…”
Section: ) Tg-lowering Drugs and Hdl-c-increasing Drugsmentioning
confidence: 99%
“…These drugs reduce both LDL cholesterol and triglycerides and raise HDL slightly. Gemfibrozil reduced myocardial infarction and stroke among men with coronary artery disease with low HDL and LDL in the Veterans Affairs HDL Intervention Trial (VA-HIT), but recent meta-analysis of fibrates suggested that it has effects on coronary events, but no effect on stroke [56,57].…”
Section: Dyslipidemiamentioning
confidence: 99%